PENDIDIKAN ISLAM MELALUI SENI VOKAL RELIGIUS (EKSPLORASI MAKNA DAN FUNGSI QASIDAH BURDAH) DI MAJELIS SHALAWAT AL ISHLAAH SUNGAI LULUT KECAMATAN SUNGAI TABUK - Muhammad Subhan; Muhammad Yusuf; Noorzanah (STKIP Subang, 2026)
In Majelis Shalawat Al Ishlaah, Sungai Lulut, Sungai Tabuk District, this study investigates the function of Qasidah Burdah as an Islamic educational medium through religious vocal art. The need to comprehend how the meanings ingrained in the verses of Qasidah Burdah contribute to the congregation's assimilation of Islamic educational principles served as the driving force behind the study. The study sought to determine the factors that facilitate and hinder the application of Qasidah Burdah, as well as to investigate its meanings and pedagogical purposes. This study used a field research design and a qualitative descriptive approach. A Qasidah Burdah vocalist, active members of the congregation, and the management of the majelis were the subjects of observations, interviews, and documentation. The results show that Qasidah Burdah is a useful tool for Islamic preaching, moral instruction, spiritual growth, maintaining Islamic customs, and fostering Islamic fraternity. The availability of translated Burdah books, a religious social setting, and community support all help to carry out this practice. The congregation's restricted access to translated materials, however, continues to be a major barrier to comprehending the passages' contents. These results show that, in community-based religious events, religious voice art can serve as a substitute medium for enhancing Islamic educational principles.